La educación como fuente de estrés para las familias con menores con síndrome de Down (Journal of Parents and Teachers, 2018)
Families with children with Down syndrome have to face new challenges that they did not expected when they started the fatherhood adventure. One of those challenges refers to the approach to the formal education of their children. The research results show that these families are more vulnerable to stress when their kids begin the school period, as well as less sense of family coherence and lower family satisfaction. It is necessary an important transformation of the educational system so that it includes all of its students offering equal learning opportunities.
Keywords: family; Down syndrome; education